In Systemic Sclerosis, Anxiety and Depression Assessed by Hospital Anxiety Depression Scale Are Independently Associated with Disability and Psychological Factors. (29th July 2013) - Del Rosso, Angela; Mikhaylova, Svetlana; Baccini, Marco; Lupi, Ilaria; Matucci Cerinic, Marco; Maddali Bongi, Susanna
Abstract : Background . Anxious and depressive symptoms are frequent in Systemic Sclerosis (SSc). Our objective is to assess their prevalence and association with district and global disability and psychological variables. Methods . 119 SSc patients were assessed by Hospital Anxiety Depression Scale (HADS). Clinical depression and anxiety were defined for HADS score cutoff ≥8. Patients were assessed for psychological symptoms (RSES, COPE-NIV), hand (HAMIS, CHFDS, fist closure, and hand opening) and face disability (MHISS, mouth opening), global disability, and fatigue (HAQ, FACIT). Results . Both depression and anxiety in SSc are 36%. Depressive patients with comorbid anxiety have higher HADS-D score than patients with depression only (P = 0.001 ). HADS-A and -D are positively correlated with global disability, hands and mouth disability, fatigue, self-esteem and avoidance coping strategy, and, only HADS-A, also with social support (P < 0.05 ). By multiple regression, HADS-D is independently associated with FACIT-F (P < 0.001 ), RSES (P < 0.001 ), and MHISS total score (P = 0.016 ), together explaining 50% of variance. HADS-A is independently associated with RSES (P = 0.006 ), COPE-NIV SA (P = 0.003 ), COPE-NIV SS (P = 0.008 ), FACIT-F (P = 0.022 ), and MHISS mouth opening (P = 0.029 ), explaining 41% of variance. Conclusions . In SSc depression and anxiety correlate to local and global disabilities and psychological characteristics. Depressive patients with comorbid anxiety have higher level of depressive symptoms.